2010
DOI: 10.4049/jimmunol.0901022
|View full text |Cite
|
Sign up to set email alerts
|

Age-Associated Decrease in TLR Function in Primary Human Dendritic Cells Predicts Influenza Vaccine Response

Abstract: We evaluated Toll-like receptor (TLR) function in primary human dendritic cells from 104 young (age 21–30) and older (≥ 65 years) individuals. We used multicolor flow cytometry and intracellular cytokine staining of myeloid (mDC) and plasmacytoid (pDC) DCs and found substantial decreases in older, compared to young individuals in TNF-α, IL-6 and/or IL-12 (p40) production in mDCs and in TNF-α and IFN-α production in pDCs in response to TLR1/2, TLR2/6, TLR3, TLR5, and TLR8 engagement in mDCs and TLR7 and TLR9 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
403
8
10

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 477 publications
(457 citation statements)
references
References 42 publications
24
403
8
10
Order By: Relevance
“…Nevertheless, recent studies have shown that TLR's role in regulating the adaptive responses can be harnessed to boost immunogenicity of influenza vaccines (e.g., TLR9 or TLR7 ligands as adjuvants). This may be particularly useful in the elderly and the immunologically naïve vaccinees 4, 33, 34, 35, 36, 37, 38, 39, 40. Our data in natural influenza provide additional support to this new vaccination approach.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Nevertheless, recent studies have shown that TLR's role in regulating the adaptive responses can be harnessed to boost immunogenicity of influenza vaccines (e.g., TLR9 or TLR7 ligands as adjuvants). This may be particularly useful in the elderly and the immunologically naïve vaccinees 4, 33, 34, 35, 36, 37, 38, 39, 40. Our data in natural influenza provide additional support to this new vaccination approach.…”
Section: Discussionmentioning
confidence: 64%
“…Factors determining TLR expression in an individual should be further studied 3, 42. We report that in some old patients (>65 years of age, P  = 0·025), despite successful cytokine and ligand stimulation studies, the number of DCs in circulation was too few and signals too weak (due to aging and/or site “migration”) to allow full‐range TLR analysis 6, 39. The conclusions were unlikely affected, however, as these were balanced between the age‐matched cases/controls ( P  = 0·768).…”
Section: Discussionmentioning
confidence: 99%
“…Notable changes contributing to immunosenescence include, among others, decreased proliferation of lymphocytes, reduced T-cell receptor repertoire, and defects in antibody production (1,2). This phenomenon contributes to an age-related increase in susceptibility to viral and bacterial infections and decreased response to vaccination (3)(4)(5).…”
mentioning
confidence: 99%
“…In the elderly, antibody responses to vaccines are slower and not as strong as those in younger people, and T-cell subpopulations are not very responsive to vaccines, which may impair the ability to achieve protective immunity after vaccination. 20,21 At an individual level the assessment of safety may be different in na€ ıve versus primed subjects: for example, pre-existing immunity to a specific antigen may cause lower or higher reactogenicity on re-exposure. The safety evaluation will also be influenced by whether the individual is immune-compromised or has underlying morbidities compared to healthy individuals, and by their physiological status: for example, during pregnancy the maternal immune system is altered to tolerate the semi-allogeneic fetus.…”
Section: Vaccines Containing Adjuvants: Key Features That Guide Safetmentioning
confidence: 99%